2015
DOI: 10.1016/j.jot.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of dynamic sitting balance tests and their correlations with functional mobility for wheelchair users with chronic spinal cord injury

Abstract: SummaryThe purpose of this study is to develop a reliable and valid tool for measuring the dynamic sitting balance of wheelchair users with spinal cord injury. The balance tests were performed in nine patients with chronic spinal cord injury (average of 17.2 years postinjury) between levels C6 and L1, while they were sitting in their wheelchairs and on a standardized stool (unsupported sitting), twice, 7 days apart. Limits of stability (LOS) and sequential weight shifting (SWS) were designed in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
1
25
1
1
Order By: Relevance
“…The moderate reliability of the SWS test can be considered to be acceptable among this population of older adults with a mean age of 88 years and some physical disability. A similar reliability (ICC=0.69) was reported in another study with a similar assessment protocol, i.e., an investigation of the dynamic sitting balance control of subjects with spinal cord injury 20 ) . The lack of familiarity with the equipment setup and testing procedures may have affected the reliability result even though familiarization trials were conducted before the actual testing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The moderate reliability of the SWS test can be considered to be acceptable among this population of older adults with a mean age of 88 years and some physical disability. A similar reliability (ICC=0.69) was reported in another study with a similar assessment protocol, i.e., an investigation of the dynamic sitting balance control of subjects with spinal cord injury 20 ) . The lack of familiarity with the equipment setup and testing procedures may have affected the reliability result even though familiarization trials were conducted before the actual testing.…”
Section: Discussionsupporting
confidence: 79%
“…The force platform could possibly be tailored to purpose using four load cells mounted on the platform to reduce the cost. Also, the size of the platform could be adjusted to suit different sizes of chair and even wheelchair 20 ) . Another issue is that it may be difficult for older adults with cognitive impairment to perform the SWS test.…”
Section: Discussionmentioning
confidence: 99%
“…The Test-Table-Test Board performed in a special stand [21, 26], special motorized plate on which a sit-ski can be placed to test athletes’ trunk stability [23] or the unique sensorized frame with mounted electrical-drive sledge to test trunk control are helpful in assessing trunk function in specific settings in paraskiing athletes. In general, balance tests (static and dynamic) [6, 9, 12, 16], variations of reach tests [14, 27], trunk inclination tests using force plates [28] and maximal static trunk strength measurement [5, 16, 17, 20] are used for trunk assessment. However, according to evidence-based classification approach, there is a need to find appropriate methods, tools or tests related to movement specificity in a given sport that would support or change the current type of trunk assessment [29].…”
Section: Introductionmentioning
confidence: 99%
“…The suitability for the study was initially specified with a telephone interview, followed by consultation with a neurosurgeon who confirmed that the participant can be included in the study. Inclusion criteria for the study participants were: (1) age 18–55 years; (2) chronic SCI (≥12 months’ post injury) [17]; (3) traumatic origin of the injury located in the cervical region, resulting in tetraplegia; (4) scoring of B or C by American Spinal Injury Association Impairment Scale (AIS); (5) able to sit unsupported on a custom-made chair. Participants were excluded from the study if they had cardiopulmonary insufficiency, cardiac pacemaker, oncological disease, epilepsy, open wounds, or metal implants in the area where FES was planned to be performed.…”
Section: Methodsmentioning
confidence: 99%